Development of an educational platform for anti-scamming and anti-phishing - Zhong, Yi (Nanyang Technological University, 2023)
Since the dot-com bubble, the internet and its associated technologies have become an increasingly large part of our daily lives. Unfortunately, the rising global usage of the internet and the expansion of cyberspace has also led to an increasing rate of cybercrimes. This is more so due to the global pandemic where many began working remotely, further increasing reliance on the internet for both work and leisure purposes. The target group for this project, Generation Z, are also known as the internet natives. Having grown up with technology and the internet as a ubiquitous presence in their lives, this tech-savvy generation relies heavily on online resources in their daily life.